Unshaped refractory material, method for producing moist unshaped refractory material and method for producing refractory liner

By using citric acid and aluminum sulfate as the binder component in the ambient refractory material and adding a small amount of water to the ambient temperature range from 1,000 to 1,200°C, the problem of strength loss in the preheating process of ambient refractory materials in the prior art is solved, and stable bonding and improved refractory performance are achieved.

CN119654300APending Publication Date: 2025-03-18REFRACTORY INTELLECTUAL PROPERTY GMBH & CO KG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380058314.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-26
Filing Date
2023-08-16
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing amorphous refractory materials consume high energy during the preheating process due to moisture evaporation, and the decomposition of organic components at high temperatures leads to strength loss, resulting in damage or damage to the refractory lining.

Method used

An amorphous refractory material comprising a refractory base component and a binder component is used, wherein the binder component consists of citric acid and aluminum sulfate, and the material forms a stable bond at ambient temperature to 1,000 to 1,200°C by adding a small amount of water.

Benefits of technology

Amorphous refractory material that is hardened only by a small amount of hydrotonic in the cold state provides stable bonding until the maximum preheating temperature is reached, avoiding strength losses caused by moisture evaporation and decomposition of organic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005263428050000141
    Figure BDA0005263428050000141
Patent Text Reader

Abstract

The invention relates to an unshaped refractory material, to a method for producing a moist unshaped refractory material and to a method for producing a refractory liner.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a monolithic refractory material, a method for producing a moist monolithic refractory material and a method for manufacturing a refractory lining.

[0002] Refractory materials are materials that can withstand high temperatures. The term "refractory" in the context of the present invention refers specifically to refractory materials with an operating temperature above 600°C, and preferably refers to refractory materials according to DIN 51060:2000-06, i.e., materials with a melt cone equivalent of >SK17. The melt cone equivalent can be determined, in particular, according to DIN EN 993-12:1997-06.

[0003] "Amorphous" refractory refers to a refractory that does not have a defined shape, i.e., a refractory that is not given a defined shape by any forming method (such as pressing). On the contrary, an amorphous refractory can be, for example, a block or some other amorphous forms. In particular, an amorphous refractory refers to a material also referred to as "refractory material" or "refractory mixture". As is well known, the amorphous refractory material in the form of a refractory material is introduced amorphously at its use location, and is only hardened, dried and heated there. In particular, the lining of high temperature aggregate can be used in the form of such a refractory material.

[0004] A typical application of monolithic refractories is their use in lining high-temperature aggregates in steel production. For example, in one of the final steps of the steelmaking process, molten steel is poured from a tundish into a cooled mold. To ensure a continuous casting process and protect the tundish's permanent lining from corrosion and erosion, the tundish is often lined with a monolithic refractory material (the so-called "wear lining mix"). Before casting begins, the wear lining mix must typically be preheated to approximately 1,000 to 1,200°C to prevent the molten steel from solidifying in the tundish at the start of the casting process. Upon reaching a temperature within this range of approximately 1,000 to 1,200°C, the monolithic refractory material begins to sinter, forming a ceramic bond and thus achieving permanent strength during the casting process. The most common wear lining mix used to line tundishes is the so-called "slurry gunning mix." However, these types of mixes have a relatively high water content. Therefore, before preheating the slurry gunning mix, it must be dried in a relatively lengthy and energy-intensive drying process. Alternatively, so-called "cold-curing mixes," also known as wear-resistant lining mixes for lining tundishes, have a low water content and do not require a separate drying process before preheating. Such cold-curing mixes are hardened by cold organic compounds. However, in the case of cold-curing mixes, preheating leads to decomposition of the organic components in the mix and, consequently, a loss of strength in the cold-curing mix in the temperature range of approximately 600 to 1,000°C (i.e., before a ceramic bond is formed). This loss of strength can lead to damage or even destruction of refractory linings based on such cold-curing mixes.

[0005] The object of the present invention is to provide a monolithic refractory material that hardens in a cold state by only adding a small amount of water and at the same time provides a stable bond until the maximum preheating temperature is reached. In particular, the monolithic refractory material should show a stable bond until the temperature at which the monolithic refractory material begins to sinter is reached. In particular, a stable bond should mean that the monolithic refractory material is substantially not damaged or even destroyed. In particular, the monolithic refractory material should allow a stable bond to be provided over a temperature range from ambient temperature to a temperature in the range of about 1,000 to 1,200°C.

[0006] In order to solve this problem, according to the present invention, there is provided a monolithic refractory material, comprising:

[0007] refractory base components; and

[0008] Adhesive component; wherein the adhesive component comprises,

[0009] citric acid; and

[0010] Aluminum sulfate; and wherein

[0011] The refractory base component exists as a mass of grains, wherein

[0012] The grains comprise a fine fraction of grains having a grain size below 0.063 mm, wherein

[0013] The fine fraction is present in a proportion within the range of 3-30 mass % based on the total mass of the refractory base component, and wherein

[0014] The fine fraction contains CaO in a proportion within the range of 1.5-10 mass %, based on the total mass of the fine fraction.

[0015] Surprisingly, it has been discovered according to the present invention that such a monolithic refractory material can provide a material that forms a stable bond with only very small additions of water within a temperature range from ambient temperature to the sintering temperature of the material. In particular, a stable bond can be provided with only very small additions of water within a temperature range from ambient temperature up to a temperature in the range of 1,000 to 1,200°C. In particular, the bond is stable within this temperature range to such an extent that a wear-resistant lining mixture for a tundish made of the monolithic refractory material according to the present invention does not experience any significant damage within a temperature range from ambient temperature up to a maximum preheating temperature in the range of approximately 1,000 to 1,200°C.

[0016] In particular, it has been found according to the invention that such a stable bond of the monolithic refractory material according to the invention can already be achieved by adding only 1.0 to 1.9 mass % of water, based on the mass of the monolithic refractory material without water.

[0017] An important finding according to the present invention is that such a stable bond can be achieved by combining a binder with the fine-grained fraction of the refractory base component according to the invention.

[0018] The refractory base component is present as a grain mass, i.e., in the form of a block material. This grain mass contains a fine fraction of grains with a particle size of less than 0.063 mm (63 μm). Based on the total mass of the refractory base component, this fine fraction with a particle size of less than 0.063 mm is present in a proportion within the range of 3-30 mass %. In addition to the proportion of the fine fraction, the fine fraction must also contain CaO in a proportion within the range of 1.5-10 mass %, based on the total mass of the fine fraction.

[0019] According to the present invention, it has been found that based on the monolithic refractory material according to the present invention, if the amount of fines is close to the range of 10-15% by mass, the bonding stability is improved. Therefore, preferably, it can be provided that the fines are present in a proportion of at least 3% by mass, more preferably at least 7% by mass, and even more preferably at least 10% by mass, in each case based on the total mass of the refractory base component. In addition, it can be provided that the fines are present in a proportion of at most 30% by mass, more preferably at most 17% by mass, and even more preferably at most 15% by mass, in each case based on the total mass of the refractory base component. In addition, it can be provided that the fines are present in a proportion in the range of 7-17% by mass, and even more preferably in a proportion in the range of 10-15% by mass, in each case based on the total mass of the refractory base component.

[0020] With regard to the proportion of CaO in the fine fraction, it has been found according to the present invention that, based on the monolithic refractory material according to the present invention, the bonding stability is improved if the amount of CaO in the fine fraction is close to the range of 2-6 mass%. Therefore, it can be preferably provided that the fine fraction contains a proportion of CaO of at least 1.5 mass%, and even more preferably at least 2 mass%, in each case based on the total mass of the fine fraction. Furthermore, it can be provided that the fine fraction contains a proportion of CaO of at most 10 mass%, more preferably at most 8 mass%, and even more preferably at most 6 mass%, in each case based on the total mass of the fine fraction. Furthermore, it can be provided that the fine fraction contains a proportion of CaO in the range of 2-8 mass%, and even more preferably in the range of 2-6 mass%, in each case based on the total mass of the fine fraction.

[0021] The proportion of the fine fraction is preferably determined by sieve analysis, particularly preferably in accordance with standard ISO 1927-3:2012-12.

[0022] According to the invention, it has been found that the stable bond that can be achieved by the monolithic refractory material according to the invention can be adversely affected by the presence of certain oxides in the fine fraction. Therefore, it can be preferably provided that certain oxides (in particular Fe2O3, Al2O3 and SiO2) are present in the fine fraction in certain maximum proportions. According to one embodiment, it is provided that the fine fraction contains the following oxides in the following proportions, each based on the total mass of the fine fraction:

[0023] CaO: 1.5-10 mass%;

[0024] Fe2O3: less than 6% by mass;

[0025] Al2O3: less than 3% by mass;

[0026] SiO2: less than 7% by mass;

[0027] MgO: balance to 100 mass %.

[0028] The proportion of CaO in the fine fraction may further be present in the proportions as described above.

[0029] The above proportions of oxides in the fine fraction are the chemical proportions of these oxides in the fine fraction. Therefore, the oxides do not need to be present in the fine fraction in pure oxide form. Preferably, the proportions of oxides in the fine fraction are determined by X-ray fluorescence analysis (XRF), preferably by standard ISO 12677:2011-10.

[0030] The binder component of the monolithic refractory material according to the present invention comprises citric acid and aluminum sulfate.

[0031] According to a preferred embodiment, the citric acid is present as a powder.

[0032] According to a further preferred embodiment, the aluminum sulfate is present as a powder.

[0033] A particular advantage of the citric acid and aluminum sulfate being present as powders is that these powders can be distributed very easily and evenly throughout the volume of the monolithic refractory material according to the invention, particularly more easily than, for example, moist components. This even distribution of the binder component over the volume of the monolithic refractory material also leads, in particular, to very uniform stability of the material after the addition of water. A further advantage of the powdered binder component is that it can prevent undesired hardening of the material according to the invention before the addition of water.

[0034] According to a preferred embodiment, the monolithic refractory material according to the present invention contains citric acid in a proportion within the range of 1.6-6% by mass, based on the total mass of the refractory base component and the binder component.

[0035] According to the present invention, it has been found that a stable bond can be achieved with the monolithic refractory material according to the present invention, particularly when citric acid is present in such proportions. According to the present invention, it has further been found that when the amount of citric acid is close to 2-3% by mass, the stable bond can be further improved, and the material according to the present invention is particularly easy to handle. Therefore, it can be preferably provided that the citric acid is present in a proportion of at least 1.6% by mass, more preferably at least 1.8% by mass, and even more preferably at least 2% by mass, in each case based on the total mass of the refractory base component and the binder component. Furthermore, it can be provided that the citric acid is present in a proportion of at most 6% by mass, more preferably at most 5% by mass, and even more preferably at most 3% by mass, each based on the total mass of the refractory base component and the binder component. Furthermore, it can be preferably provided that the citric acid is present in a proportion in the range of 1.8-5% by mass, and more preferably in the range of 2-3% by mass, in each case based on the total mass of the refractory base component and the binder component.

[0036] According to a preferred embodiment, the aluminum sulfate is present in the form of hydrated aluminum sulfate. Preferably, the hydrated aluminum sulfate hydrate is in the form of Al2(SO4)3·xH2O, wherein x is in the range of 14-16.

[0037] According to a further preferred embodiment, the monolithic refractory material according to the present invention contains aluminum sulfate in a proportion within the range of 1-5% by mass, calculated as hydrated aluminum sulfate (Al2(SO4)3·14H2O) and based on the total mass of the refractory base component and the binder component.

[0038] According to the present invention, it has been found that a stable bond can be achieved with the monolithic refractory material according to the present invention, particularly when aluminum sulfate is present in such proportions. According to the present invention, it has further been found that when the amount of aluminum sulfate approaches a proportion of 2-3% by mass, the stable bond can be further improved, and the material according to the present invention is particularly easy to handle. Therefore, it can be preferably provided that aluminum sulfate is present in a proportion of at least 1% by mass, and even more preferably in a proportion of at least 2% by mass, in each case calculated as hydrated aluminum sulfate (Al2(SO4)3·14H2O) and based on the total mass of the refractory base component and the binder component. Furthermore, it can be provided that aluminum sulfate is present in a proportion of at most 5% by mass, more preferably at most 4% by mass, and even more preferably at most 3% by mass, in each case calculated as hydrated aluminum sulfate (Al2(SO4)3·14H2O) and based on the total mass of the refractory base component and the binder component. Furthermore, it can therefore be preferably provided that aluminum sulfate is present in a proportion in the range of 1 to 4 mass %, and more preferably in a proportion in the range of 2 to 3 mass %, calculated in each case as hydrated aluminum sulfate (Al2(SO4)3·14H2O) and based on the total mass of the refractory base component and the binder component.

[0039] As mentioned above, the binder components in the form of citric acid and aluminum sulfate can be present in very small proportions in the monolithic refractory material according to the present invention. The advantage of such a small binder proportion is that premature hydration and hardening of the material according to the present invention can be avoided, thereby making the monolithic refractory material according to the present invention particularly easy to handle, in particular, easy to store and transport.

[0040] The refractory base component constitutes the refractory raw material basis of the monolithic refractory material according to the present invention. Preferably, the refractory base component comprises one or more refractory raw materials.

[0041] Particularly preferably, the refractory base component is in the form of a basic refractory base component. As is well known, basic refractory components are composed of raw materials whose main oxide is MgO (e.g. raw materials in the form of magnesium oxide, dolomite or olivine). Therefore, the refractory base component (in particular the basic refractory base component) preferably comprises one or more basic refractory raw materials.

[0042] According to a preferred embodiment, the refractory base component comprises at least one of the following refractory raw materials: magnesia and olivine.

[0043] Particularly preferably, the refractory raw material in the form of magnesium oxide is present as sintered magnesium oxide.

[0044] According to a particularly preferred embodiment, the refractory base component comprises magnesium oxide, in particular sintered magnesium oxide.

[0045] According to a preferred embodiment, the monolithic refractory material comprises sintered magnesia in a proportion of at least 50% by mass, based on the total mass of the base component. In the case where the refractory base component consists of magnesia, the monolithic refractory material preferably comprises such a proportion of sintered magnesia.

[0046] In the case where the refractory base component comprises the refractory raw materials magnesium oxide and olivine, according to a preferred embodiment, the refractory base component comprises magnesium oxide (in particular sintered magnesium oxide) and olivine in the following mass proportions, in each case based on the total mass of the refractory base component: magnesium oxide in the range of 10-90 mass% and olivine in the range of 90-10 mass%; more preferably magnesium oxide in the range of 20-60 mass% and olivine in the range of 80-40 mass%; even more preferably magnesium oxide in the range of 30-50 mass% and olivine in the range of 70-50 mass%.

[0047] According to a preferred embodiment, the refractory base component comprises the following oxides in the following proportions, each based on the total mass of the refractory base component:

[0048] CaO: 0.5-20 mass%;

[0049] Fe2O3: less than 6% by mass;

[0050] Al2O3: less than 3% by mass;

[0051] SiO2: less than 35% by mass;

[0052] MgO: balance to 100 mass %.

[0053] According to a further preferred embodiment, the refractory base component comprises the following oxides in the following proportions, each based on the total mass of the refractory base component:

[0054] CaO: 0.5-20 mass%;

[0055] Fe2O3: less than 6% by mass;

[0056] Al2O3: less than 3% by mass;

[0057] SiO2: 8-30 mass%;

[0058] MgO: 60-80 mass %.

[0059] The refractory base component may consist of the above-mentioned oxides, in particular in the case where the refractory base component consists of sintered magnesia and olivine.

[0060] According to a particularly preferred embodiment, the refractory base component comprises the following oxides in the following proportions, each based on the total mass of the refractory base component:

[0061] CaO: 0.5-20% by mass, preferably 2-6% by mass;

[0062] Fe2O3: less than 6% by mass;

[0063] Al2O3: less than 3% by mass;

[0064] SiO2: less than 5.5% by mass;

[0065] MgO: balance to 100 mass %.

[0066] The refractory base component may consist of the above-mentioned oxides, in particular in the case where the refractory base component consists of sintered magnesium oxide.

[0067] The above ratios of oxides in the refractory base component are the chemical ratios of these oxides in the refractory base component. Therefore, the oxides do not need to be present in the refractory base component in the form of pure oxides. Preferably, the ratios of oxides in the refractory base component are determined by X-ray fluorescence analysis (XRF), preferably by standard ISO 12677:2011-10.

[0068] The oxidic composition of the entire refractory base component may differ from the oxidic composition of the fine fraction of the refractory base component. In particular, the proportion of CaO in the entire base refractory component may also differ from the proportion of CaO in the fine fraction of the refractory base component.

[0069] The monolithic refractory material according to the present invention may contain other components. For example, the monolithic refractory material may contain at least one prior art sintering aid, such as boric acid, in a proportion, for example, in the range of 0.1-1.0 mass % based on the total mass of the refractory base component, the binder component and the at least one sintering aid.

[0070] Another subject of the present invention is a method for producing moist monolithic refractory materials, comprising the following steps:

[0071] Providing a monolithic refractory material according to the present invention;

[0072] Water is added to the monolithic refractory material.

[0073] Adding water to the monolithic refractory material according to the present invention causes a reaction in the monolithic refractory material, which results in bonding of the materials.

[0074] In this regard, it is also particularly advantageous that both binder components, citric acid and aluminum sulfate, are characterized by high solubility in water, which is why the bonding reaction is initiated by the addition of water. This produces an acidic solution in the monolithic refractory material that is able to dissolve the cations of the refractory base component, particularly calcium cations, thereby increasing the pH of the solution and precipitating a three-dimensional bonding phase matrix with distinct citrate-sulfate phases. This achieves stable bonding even at ambient temperature. The inventors hypothesize that this very stable bonding phase matrix based on the refractory material according to the invention is enhanced, in particular, by the very easy solubility of cations from the fine fraction of the refractory base component (particularly calcium cations and possibly magnesium cations), resulting in a rapid and intense increase in pH and thus enhanced bonding phase formation. However, the reasons for this very rapid and intense formation of the bonding phase matrix in the material according to the invention are currently the subject of further investigation. During subsequent heat treatment of the monolithic refractory material mixed with water, in particular, for example, during preheating of the material in a tundish, the organic binder components (particularly citric acid) can decompose at temperatures up to approximately 600°C. However, an advantage of the material according to the invention is that the binder structure consisting of the sulfate-containing phase is maintained up to a temperature of at least about 1,000 to 1,200° C. This means that a stable bond of the monolithic refractory material can also be maintained in the temperature range of about 600° C. to about 1,000 / 1,200° C.

[0075] Preferably, provision is made that, when carrying out the method according to the present invention, water is added to the monolithic refractory material in a proportion within a range of 1.0-1.9 mass %, based on the total mass of the refractory base component and the binder component of the monolithic refractory material free of water.

[0076] According to the present invention, it was found that by making the added water content close to a proportion in the range of 1.2-1.8 mass%, the stable bonding and handling of the monolithic refractory material mixed with water can be further improved. According to a particularly preferred embodiment, therefore, it is provided that water is added to the monolithic refractory material in a proportion in the range of 1.2-1.8 mass%, based on the total mass of the refractory base component and the binder component of the monolithic refractory material without water.

[0077] A further subject matter of the present invention is a moist monolithic refractory material produced by the method according to the invention.

[0078] After adding water to the monolithic refractory material according to the present invention, the wet monolithic refractory material can be used in particular in the form of a monolithic refractory material (ie in the form of a so-called refractory material). In particular, the wet monolithic refractory material can be used to line a tundish.

[0079] Another subject of the present invention is to provide a monolithic refractory material according to the invention, which further comprises water.

[0080] Preferably, as described above, the monolithic refractory material contains water in a proportion within the range of 1.0-1.9 mass %, and even more preferably within the range of 1.2-1.8 mass %, in each case based on the total mass of the refractory base component and the binder component excluding water.

[0081] Another subject matter of the present invention is the use of a monolithic refractory material according to the invention (particularly to the extent that the monolithic refractory material also contains water) for lining a surface. This use can particularly be provided that the surface is the surface of a vessel for containing molten steel, in particular the surface of a tundish.

[0082] Another subject of the invention is a method for producing a refractory lining comprising the following steps:

[0083] Providing a monolithic refractory material further comprising water according to the present invention;

[0084] A monolithic refractory material containing water is applied to the surface.

[0085] The surface may in particular be the surface of a vessel for containing molten steel, in particular the surface of a tundish.

[0086] Further features of the invention are apparent from the claims and the examples of embodiment of the invention described below.All features of the invention can be combined with one another in any desired manner, either individually or in combination.

[0087] Exemplary embodiments of the present invention and comparative examples are explained in more detail below.

[0088] Exemplary embodiments

[0089] According to a first embodiment, a monolithic refractory material according to the present invention is provided, which has the following composition according to Table 1:

[0090] Table 1

[0091] Components Mass fraction [mass %] Sintered magnesium oxide ≤2.36mm 94.5 aluminum sulfate 2.5 Citric acid 2.5 Boric acid 0.5

[0092] The mass fractions according to Table 1 relate in each case to the sum of all components of the monolithic refractory material according to Table 1 .

[0093] Sintered magnesia represents a basic refractory component of the monolithic refractory material. Due to its composition based on sintered magnesia, this refractory base component represents a basic refractory base component.

[0094] Aluminum sulfate and citric acid were each in powder form. Aluminum sulfate existed as aluminum sulfate hydrate in the form of Al2(SO4)3·14H2O. The mass fraction of aluminum sulfate in the materials shown in Table 1 was calculated based on such aluminum sulfate hydrate.

[0095] The sintered magnesia in the monolithic refractory according to Table 1 has a chemical composition according to Table 2:

[0096] Table 2

[0097] oxides Mass fraction [mass %] MgO 93.1 <![CDATA[Al2O3]]> 0.4 <![CDATA[SiO2]]> 3.1 CaO 2.7 <![CDATA[Fe2O3]]> 0.6 other 0.1

[0098] In each case, the mass fractions according to Table 2 relate to the total mass of sintered magnesium oxide.

[0099] The mass fraction of oxides was determined by X-ray fluorescence analysis according to ISO 12677:2011-10. All other oxide data given below were also determined according to this standard.

[0100] The sintered magnesia according to Table 1 has a fine fraction with a particle size below 0.063 mm with a proportion of 11.5% by mass, based on the total mass of the sintered magnesia. The proportion of the fine fraction was determined by sieve analysis according to ISO 1927-3:2012-12.

[0101] The fine fraction of sintered magnesium oxide has a chemical composition according to Table 3:

[0102] Table 3

[0103] oxides Mass fraction [mass %] MgO 93.4 <![CDATA[Al2O3]]> 0.1 <![CDATA[SiO2]]> 2.9 CaO 3.1 <![CDATA[Fe2O3]]> 0.5

[0104] The monolithic refractory material constituted as described above was admixed with 1.5% by mass of water based on the total mass of the material excluding water, and mixed, thereby obtaining an embodiment of the moist monolithic refractory material according to the present invention.

[0105] In order to be able to determine the strength of the moist monolithic refractory material, cylindrical test specimens of the material were prepared by filling and removing a cup. These test specimens were then allowed to harden for 45 minutes.

[0106] After 45 minutes, the test specimens were inspected for dimensional stability and strength. All test specimens were found to be fully hardened. Hand damage to the test specimens was not a problem. The edges of the specimens were stable and resistant to wear.

[0107] Finally, the cold crushing strength (CCS) according to DIN EN ISO 1927-6:2013-04 of the test specimens was investigated when heated in a temperature range from ambient temperature to 1,200° C. The results of this series of tests are shown in Table 4:

[0108] Table 4

[0109] Temperature [℃] <![CDATA[CCS[N / mm 2 ]]]> 25 6.55 110 10.85 250 12.75 400 5.45 600 4.70 800 3.30 900 3.50 1,000 3.50 1,200 6.75

[0110] In particular, in a temperature range from ambient temperature up to temperatures in the range of 1,000 to 1,200° C., a stable bond can be provided by only very small additions of water.

[0111] The test results clearly show that despite a low water content of only 1.5%, a stable bond can be provided over the entire temperature range from ambient temperature (25°C) to 1,200°C, as reflected by the CCS value.

[0112] Comparative Example

[0113] For the purpose of comparison, another monolithic refractory material is provided, which is not an embodiment of the present invention (comparative example). In this regard, the monolithic refractory material according to the comparative example has a composition according to Table 1. However, the sintered magnesia has a different chemical composition than the sintered magnesia according to Table 2, i.e., has the following chemical composition according to Table 5:

[0114] Table 5

[0115] oxides Mass fraction [mass %] MgO 94.6 <![CDATA[Al2O3]]> 0.3 <![CDATA[SiO2]]> 1.3 CaO 0.5 <![CDATA[Fe2O3]]> 2.3 other 1.0

[0116] In the comparative example, the sintered magnesium oxide has a fine fraction with a particle size of less than 0.063 mm, which accounts for 10.9% by mass, based on the total mass of the sintered magnesium oxide. The chemical composition of the fine fraction is also different from that of the exemplary embodiment of the present invention. Within this range, the fine fraction has a chemical composition according to Table 6:

[0117] Table 6

[0118] oxides Mass fraction [mass %] MgO 94.4 <![CDATA[Al2O3]]> 0.8 <![CDATA[SiO2]]> 1.1 CaO 0.5 <![CDATA[Fe2O3]]> 2.4 other 0.9

[0119] The monolithic refractory material according to this comparative example was mixed with 1.5% by mass of water, processed and formed into a test specimen in the same manner as in the exemplary embodiment of the present invention described above. In addition, in the same manner as in the exemplary embodiment of the present invention, dimensional stability and strength were then checked after 45 minutes. It was then found that the test specimen exhibited certain dimensional stability, but had no strength at all. On the contrary, it was shown that the test specimen was so loose that even when gently touched with a finger, they completely disintegrated.

[0120] Due to this practically nonexistent stability at ambient temperature, the monolithic refractory material according to the comparative example proves unsuitable for any technical application. This also applies particularly to the use of such material in, for example, a tundish, since a certain stability at room temperature is required to hold (i.e., adhere) the material to the tundish sidewalls. If the material does not adhere to the tundish sidewalls, heating it to higher temperatures is technically useless. Furthermore, it must be assumed that the stability decreases even further at elevated temperatures.

[0121] Other exemplary embodiments

[0122] Several exemplary embodiments of monolithic refractory materials according to the present invention were prepared to determine their strength development at room temperature. These materials had substantially the same composition as the exemplary embodiments described above, with only the amount of binder in the material, i.e., the amount of aluminum sulfate and citric acid, being varied. A total of five embodiments of such materials were prepared, designated 01 to 04 in Table 7:

[0123] Table 7

[0124]

[0125] The test results for dimensional stability and strength are given in the last row under "Results". The corresponding numbers represent the following test results:

[0126] 3: The test specimen was found to have a rough surface and loose grains. The specimen may be slightly deformed by light finger contact.

[0127] 2: The test specimen shows good strength. Deformation and damage are only possible under high pressure. Hand-worn specimen edges may cause wear.

[0128] 1: The test specimen was found to be completely hardened. Hands did not damage the test specimen. The edge of the specimen was stable and resistant to wear.

[0129] This shows that the best results in terms of dimensional stability and strength are observed when aluminum sulfate and citric acid are each present in a ratio of 2.5% by mass.

Claims

1. A monolithic refractory material, comprising: 1.1 refractory base components; and 1.2 Adhesive component; wherein the adhesive component comprises 1.2.1 citric acid; and 1.2.2 Aluminum sulfate; and wherein 1.3 The refractory base component exists as a grain block, wherein 1.3.1 The grains include a fine fraction of grains with a grain size of less than 0.063 mm, wherein 1.3.1.1 The fine fraction is present in a proportion in the range of 3-30 mass % based on the total mass of the refractory base component, and wherein 1.3.1.2 The fine fraction contains CaO in a proportion within the range of 1.5-10 mass % based on the total mass of the fine fraction.

2. The monolithic refractory material according to claim 1, comprising citric acid in a proportion within a range of 1.6-6 mass % based on the total mass of the refractory base component and the binder component.

3. The monolithic refractory material according to at least one of the preceding claims, wherein the citric acid is present as a powder.

4. The monolithic refractory material according to at least one of the preceding claims, wherein the aluminum sulfate is present in the form of hydrated aluminum sulfate.

5. The monolithic refractory material according to at least one of the preceding claims, comprising aluminum sulfate in a proportion in the range of 1-5% by mass, calculated as hydrated aluminum sulfate (Al2(SO4)3·14H2O) and based on the total mass of the refractory base component and the binder component.

6. The monolithic refractory material according to at least one of the preceding claims, wherein the aluminum sulfate is present as a powder.

7. The monolithic refractory material according to at least one of the preceding claims, wherein the fine fraction comprises the following oxides in the following proportions, each based on the total mass of the fine fraction: CaO: 1.5-10 mass%; Fe2O3: less than 6 mass%; Al2O3: less than 3 mass%; SiO2: less than 7% by mass; MgO: balance to 100 mass %.

8. The monolithic refractory material according to at least one of the preceding claims, wherein the refractory base component comprises at least one of the following refractory raw materials: magnesia and olivine.

9. The monolithic refractory according to claim 8, comprising magnesium oxide in a proportion of at least 50 mass % based on the total mass of the base component.

10. The monolithic refractory material according to at least one of the preceding claims, wherein the refractory base component comprises the following oxides in the following proportions, each based on the total mass of the refractory base component: CaO: 0.5-20 mass%; Fe2O3: less than 6 mass%; Al2O3: less than 3 mass%; SiO2: less than 35 mass%; MgO: balance to 100 mass %.

11. A method for producing a moist monolithic refractory material, comprising the steps of: A. Providing a monolithic refractory material according to at least one of claims 1 to 10; B. Adding water to the monolithic refractory material.

12. The method according to claim 11, wherein 1.0-1.9 mass% of water is added to the monolithic refractory material based on the total mass of the refractory base component and the binder component of the monolithic refractory material excluding water.

13. The monolithic refractory material according to at least one of claims 1 to 10, further comprising water.

14. A method of manufacturing a refractory lining comprising the steps of: A. providing the monolithic refractory material according to claim 13; B. Applying the monolithic refractory material to a surface.

15. The method of claim 14, wherein the monolithic refractory material is applied to the surface of a tundish.